2017
DOI: 10.1080/03004430.2017.1385608
|View full text |Cite
|
Sign up to set email alerts
|

The relations between maternal mind-mindedness, parenting stress and obstetric history among Chinese mothers

Abstract: Relations between maternal mind-mindedness, parenting stress and obstetric history were investigated in a Chinese sample comprising of 96 mother-infant dyads (infants' mean age = 15.95 months, mean maternal age = 30 years). Parenting stress and obstetric history were assessed through questionnaires while mind-mindedness was observed through a 10minute video recording of mother-infant interactions. Results indicated that among mothers who perceived the pregnancy to have been difficult, those who had planned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…As reviewed in the introduction, previous literature suggests that maternal MM could be affected by negative and traumatic experiences during pregnancy and childbirth (Camisasca, Procaccia, Miragoli, Valtolina, & Blasio, 2017; Dai et al., 2019). Experiencing pregnancy and labor as negative can distort early representations of the child, as the mother does not feel attunement with the newborn from the outset (Meins et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed in the introduction, previous literature suggests that maternal MM could be affected by negative and traumatic experiences during pregnancy and childbirth (Camisasca, Procaccia, Miragoli, Valtolina, & Blasio, 2017; Dai et al., 2019). Experiencing pregnancy and labor as negative can distort early representations of the child, as the mother does not feel attunement with the newborn from the outset (Meins et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on this topic (Dai et al., 2019; Meins et al., 2011) confirmed that in Western and non‐Western cultures, the positive recollection of pregnancy and childbirth makes mothers more likely to get attuned to their infants’ mental state and to show AMRC during dyadic interactions. Furthermore, mothers who recalled a highly positive emotional reaction in the first contact with the newborn later reported less parenting stress (Dai et al., 2019). Furthermore, when addressing negative pregnancy and birth experiences, Camisasca, Procaccia, Miragoli, Valtolina and Di Blasio (2017) indicated that mothers reporting childbirth‐related posttraumatic stress symptoms were more likely to make fewer mind‐related comments in the interaction with their children aged 17 months.…”
Section: Introductionmentioning
confidence: 95%
“…Findings indicate that neither flood-related objective hardship, nor PTS symptoms, was associated with variability in maternal mind-mindedness, which has implications both for the etiology of mind-mindedness, and the mechanisms by which stress during pregnancy may influence child outcomes. Firstly, a view of maternal mind-mindedness as specific to a particular mother-child relationship suggests that this quality may originate during the prenatal period and be influenced by experiences during pregnancy (Arnott & Meins, 2008;Dai et al, 2017;McMahon et al, 2016;Meins et al, 2011). Current findings suggest that, while maternal mind-mindedness may indeed have precursors in the mother's willingness to represent her fetus as a child with a future (Arnott & Meins, 2008;McMahon et al, 2016), it may be her own attachment style (Madigan, Hawkins, Plamondon, Moran, & Benoit, 2015), rather than conditions surrounding her pregnancy, that may exert the strongest influence on her propensity to consider her fetus as a future infant with a mind.…”
Section: Discussionmentioning
confidence: 99%
“…showing an association of mind-mindedness with prenatal factors associated with a mother's subjective experience of pregnancy (e.g., evaluations, maternal-fetal attachment), but not objective prenatal factors (e.g., obstetric complications) (Arnott & Meins, 2008;Dai et al, 2017;McMahon et al, 2016;Meins et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation